Unsuccessful quitters among smokers in stop smoking services in Perlis : the proportion and its associated factors - Ismail, Muhammad Ikhwan (2020)
Background: Tobacco smoking is one of the modifiable factor that contribute to non-communicable disease worldwide. Thus as a preventive strategy, one of the WHO Framework Convention on Tobacco Control (FCTC) recommendation is to provide stop smoking services in health facility especially in primary health care. Stop Smoking Services was introduced in Malaysia in 2004. However, the success rate has been mixed and not much has been known about the associated factors. Therefore it is important to identify risk group to improve the outcome of the treatment in the Stop Smoking Services. Objectives: This study aimed to measures the proportion of, and identifies the factors associated with, unsuccessful quitters among smokers in Stop Smoking Services in government health clinics in Perlis. Methodology: This was a retrospective record review study using data from the Stop Smoking Services registry and patient file card between January 2017 and Jun 2019. The registry system started from 2004 aiming to standardize the management of stop smoking clients and to monitor the outcome of the services. It included 427 data that fulfil criteria. All clients who registered with stop smoking services in Perlis health clinics were included. Multiple logistic regression was used to assess for factors associated with unsuccessful quitters. Factor that included were age, gender, ethnicity, marital status, education level, hypertension disease, number of clinic session, previous attempt to quit, duration of smoking and type of treatment. At univariate level, factors with p-value <0.25 was chosen for multiple logistic regression. Multiple logistic regression was presented as adjusted odd ratio (AdjOR), 95% CI and Wald statistic. Unsuccessful quitters define as clients who fail to quit smoking within 6 months of follow up. Results: Prevalence of unsuccessful quitters among smokers who attended stop smoking clinics in Perlis from January 2017 to Jun 2019 was 63%. Multiple logistic regression showed that those who attended at least four times the clinic session (AdjOR 0.15; 95% CI: 0.10, 0.24) and being married (AdjOR: 0.36; 95%CI: 0.14, 0.93) contributed to unsuccessful quitters among smokers. They predicted the likelihood of being successful instead of unsuccessful. Conclusion: The proportion of unsuccessful quitters among smoker in Stop Smoking Services in Perlis health clinic was high. The number of clinic session attended and marital status were factors associated with unsuccessful quitters among smoker in Perlis.